Transforming Standard of Care for Spine Surgery: Integration of an Online Single-Session Behavioral Pain Management Class for Perioperative Optimization - Davin, Sara A.; Savage, Jason; Thompson, Nicholas R.; Schuster, Andrew; Darnall, Beth D. (Frontiers in Pain Research, 2022)
Estimates suggest that 10-40% of lumbar spine surgery patients experience persistent post-surgical pain (PPSP). PPSP is associated with 50% greater healthcare costs1, along with risks of emotional distress and impaired quality of life. In 2019, U.S. Health and Human Services identified brief and digital behavioral treatments as important for pain management after surgery2. Indeed, brief behavioral pain treatments delivered in the perioperative period may offer patients a low burden opportunity to acquire essential pain coping strategies for enhanced surgical recovery. Additionally, the COVID-19 pandemic has diminished in-person pain treatment access during extended perioperative time frames, thus underscoring the need for on-line options and home based care. This report describes the integration of an online, live-instructor delivered single-session pain self-management intervention (Empowered Relief) into the standard of care for lumbar spine surgery. Here, we apply the RE-AIM framework; describe systems implementation of the Empowered Relief intervention in a large, academic medical center during the COVID-19 pandemic; describe operational challenges and financial considerations; and present patient engagement data. Finally, we discuss the scalable potential of Empowered Relief and other single-session interventions in surgical populations, their importance during extended perioperative periods, practical and scientific limitations, and new directions for future research on this topic.